2016
DOI: 10.1111/jocn.13381
|View full text |Cite
|
Sign up to set email alerts
|

Older people and their care partners’ experiences of living with mental health needs: a focus on collaboration and cooperation

Abstract: Nurses and care workers need to consider how 'tasks' can be used as a vehicle for creating emotional connections with service users. Service managers and leaders need to consider the implications of discontinuities in care on service user, care partner, nurses and care workers experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 31 publications
1
30
2
Order By: Relevance
“…Several studies highlighted that stigma and ageism were determinants of the usage of mental health support in older people with FMI (Byers et al, ; McCormack & Skatvedt, ; Muir‐Cochrane et al, ; Palinkas et al, ). Byers et al's () study revealed that some older people with FMI reported being embarrassed to discuss their mental health needs and therefore did not access mental health services.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies highlighted that stigma and ageism were determinants of the usage of mental health support in older people with FMI (Byers et al, ; McCormack & Skatvedt, ; Muir‐Cochrane et al, ; Palinkas et al, ). Byers et al's () study revealed that some older people with FMI reported being embarrassed to discuss their mental health needs and therefore did not access mental health services.…”
Section: Resultsmentioning
confidence: 99%
“…Develop processes of engagement, education, information sources and facilitators (McCormack & Skatvedt, )…”
Section: Resultsmentioning
confidence: 99%
“…Many factors are positively associated with ageing in place, such as better financial resources, better familiarity with people and better amenities in the community, all of which can provide a sense of belonging (Sabia, ; Wiles, Leibing, Guberman, Revee, & Allen, ). However, earlier studies show that older people with mental health problems who live at home, and their care partners, make up a silent group with few healthcare requirements (McCormack & Skatvedt, ; Skatvedt & Andvig, ), possibly indicating that this care partner group hesitates to ask for help and instead chooses to carry out care tasks themselves.…”
Section: Introductionmentioning
confidence: 99%
“…that older people with mental health problems who live at home, and their care partners, make up a silent group with few healthcare requirements (McCormack & Skatvedt, 2016;Skatvedt & Andvig, 2014), possibly indicating that this care partner group hesitates to ask for help and instead chooses to carry out care tasks themselves.…”
mentioning
confidence: 99%